SUBORDINASI PEREMPUAN DAN IMPLIKASINYA TERHADAP RUMAH TANGGA - Syafe’i, Imam (Universitas Islam Negeri Raden Intan Lampung, 2015)
THE SUBORDINATION OF WOMEN AND ITS IMPLICATION TO HOUSEHOLD: Women in general are in the oppressed, persecuted and deprived. Islam teaches the respect feeling and cherishes one other. This paper examines the perspective of feminism. The subordination of women is rooted in a set of constraints and cultural practices that hinder women’s access to the opportunity to compete fairly with men. This process happened through the customs in the family, community, education institutional that provide the role to place the women in number 2 in public. Therefore, the women leadership in domestic and public area can’t be defined as the superior especially in physically sense but also it can be interpreted the capability of the women. So, basically everybody has the ability to be a leader. This thing continued to be done by the group of feminism in spite of getting challenges and some obstacle of the group that focus on the patriarchal culture and religion with the understanding of religious –legal- formal. The group aligns the role of women by men so that there is no subordination, marginalization, violence, persecution and injustice which have covered the independence of the rights of women.